Giant Cysticercosis of the Right Kidney: A Case Report - Yumeng Zhang; Huaqing Tan; Xukun Gao; Yuxuan Wang; Yuntai Cao (Clinical Case Reports)
ABSTRACT Cysticercosis, although reported in several parts of the body, especially the liver, lesions occurring in the kidney are particularly rare. We report a 58‐year‐old female patient with intermittent epigastric pain, who was found to have a huge occupancy of the right kidney on computed tomography (CT) and magnetic resonance imaging (MRI), which was confirmed to have a predominantly cystic component, with no clear enhancement on CT images after injection of contrast medium, and significant enhancement of the peritoneum and septum visible on MRI. This case reports a case and its rarity of cysticercosis occurring in the kidney.